Fluorescence and molecular weight dependence of disinfection by-products formation from extracellular organic matter after ultrasound irradiation. (May 2023) - Peng, Yazhou; Yang, Xiongwei; Huang, Hongqi; Su, Qitao; Ren, Bozhi; Zhang, Zhi; Shi, Xueping
Abstract: Algal blooms have a negative impact on the safety of drinking water. Ultrasonic radiation technology is an "environment-friendly" technology that is widely used in algae removal. However, this technology leads to the release of intracellular organic matter (IOM), which is an important precursor of disinfection by-products (DBPs). This study investigated the relationship between the release of IOM in Microcystis aeruginosa and the generation of DBPs after ultrasonic radiation as well as analyzed the generation mechanism of DBPs. Results showed that the content of extracellular organic matter (EOM) in M. aeruginosa increased in the order of 740 kHz >1120 kHz >20 kHz after 2 min of ultrasonic radiation. Organic matter with a molecular weight (MW) greater than 30 kDa increased the most, including protein-like, phycocyanin (PC) and chlorophyll a, followed by small-molecule organic matter less than 3 kDa, mainly humic-like substances and protein-like. DBPs with an organic MW range of less than 30 kDa were dominated by trichloroacetic acid (TCAA), while those with an MW greater than 30 kDa had the highest trichloromethane (TCM) content. Ultrasonic irradiation changed the organic structure of EOM, affected the amount and type of DBPs, and tended to generate TCM. Graphical abstract: Image 1 Highlights: EOM-derived THM and HAA strongly depend on the fluorescence and MW properties. Ultrasonic radiation can release more extracellular macromolecular organic matter. Ultrasonic chemical effect destroys the structure of macromolecular organic matter. The change of EOM characteristics promotes the generation of more THMs.